Genome-wide association analysis of anti-TNF-α treatment response in Chinese patients with psoriasis - Ren, Yunqing; Wang, Ling; Dai, Huatuo; Qiu, Guiying; Liu, Jipeng; Yu, Dianhe; Liu, Jianjun; Lyu, Cheng-Zhi; Liu, Lunfei; Zheng, Min (Frontiers in Pharmacology, 2022)
Background: TNF-α inhibitors are effective biological agents for treating psoriasis, but the treatment responses differ across patients. This study aimed to identify genetic biomarkers of anti-TNF-α response in Chinese psoriasis patients using a genome-wide association approach. Methods: We recruited two independent cohorts of Chinese psoriasis patients administered etanercept biosimilar (with or without methotrexate). We identified 61 and 87 good responders (PASI improvement ≥75%), 19 and 10 poor responders (PASI improvement <50%) after 24 weeks treatment in the two cohorts, respectively. Then we performed genome-wide association studies (GWAS) on anti-TNF-α response in each cohort independently, followed by a fixed-effects inverse-variance meta-analysis in the 148 good and 29 poor responders. Results: We tested genetic associations with >3 million genetic variants in either cohort. Meta-analysis identified significant associations within seven loci at P < 10-5, which also showed consistent association evidence in the two cohorts. These seven loci include rs2431355 (OR=6.65, P=4.46×10-7, IQGAP2-F2RL2 on 5q13.3), rs11801616 ( OR= 0.11, P=1.75 ×10-6, SDC3 on 1p35.2), rs3754679 ( OR= 0.17, P=7.71×10-6, CNOT11 on 2q11.2), rs13166823 ( OR= 0.09, P=3.71×10-6, IRF1-AS1 on 5q31.1), rs10220768 (OR= 5.49, P=1.48 ×10-6, NPAP1 on 15q11.2), rs4796752 (OR=5.56, P=1.49×10-6, KRT31 on 17q21.2), and rs13045590 (OR=0.08, P=9.67×10-7, CTSZ on 20q13.3). Of the seven SNPs, six SNPs showed significant eQTL effect (p<1×10-6) for several genes in multiple tissues. Conclusion: These results suggest novel biological mechanisms and potential biomarkers for the response to anti-TNF therapies. These findings warrant further validation.